Pengaruh Diferensiasi Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Shopee: (Studi Pada Masyarakat Kota Denpasar) - Adi Putra, I Komang Kurnia; Putri Agustina, Made Dian (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study aims to determine the effect of product differentiation and service quality on Shopee customer satisfaction. The location of this research was conducted on customers residing in Denpasar, with a sample of 60 respondents. The data analysis techniques used are multiple linear regression analysis, determination coefficient test, T test and F test. The results obtained in this study are: 1) Product differentiation has a positive and significant effect on Shopee customer satisfaction with a significance value of 0.001 with a regression coefficient value of 0.247 and a calculated t value > t table (3.688 > 1.672). 2) Service quality has a positive and significant effect on Shopee customer satisfaction with a significance value of 0.000 with a regression coefficient value of 0.345 and a t value calculated > t table (4.143 > 1.672). 3) Product differentiation and service quality simultaneously have a positive and significant effect on Shopee customer satisfaction with a significance value of 0.000 and an F value calculated > F table (43,779 > 3.16). The advice in this study is to fill in features that are easy for customers to use, provide protection for customers who shop at Shopee to be safe during payment and stricter in shipping purchased goods.